Comprehensive Assessment of the Impact of Prolonged Stressful Events on Quality of Life and Its Components among Medical Students - Ogorenko, Вікторія; Kokashynskyi, Віктор; Shornikov , Андрій; Kokashynska, Ксенія (Psychosomatic Medicine and General Practice, 2025)
Introduction. Prolonged stress-inducing events such as the COVID-19 pandemic and ongoing war have a significant impact on mental health and quality of life. Medical students represent a particularly vulnerable group, as they are simultaneously involved in academic training and clinical work under conditions of chronic stress. Assessing their psycho-emotional well-being during different periods of societal upheaval is essential for developing effective support strategies. Purpose. To assess the impact of prolonged stress events (the COVID-19 pandemic and wartime conditions) on the mental health and quality of life of medical students. Materials and Methods. The study included 128 fourth- and fifth-year students of Dnipro State Medical University: 67 participants in 2019 (prior to the pandemic and full-scale invasion) and 61 participants in 2024. Clinical-psychopathological and psychodiagnostic evaluations were conducted using the following scales: PHQ-9, Q-LES-Q, DEBQ, Spielberger State-Trait Anxiety Inventory, and MAST. Statistical analysis was performed using Statistica and MedCalc software, applying nonparametric methods, correlation analysis, logistic regression, and the calculation of relative risks and odds ratios. Results. The overall quality of life index did not differ statistically between the groups. However, in 2024 there was a decline in subjective well-being across several psycho-emotional components, especially among male students (health, self-control, optimism), alongside improvements in professional-motivational indicators among females (work, achievements). Statistically significant associations were identified between lower quality of life and the presence of depression, anxiety, and external eating behavior. In 2024, the impact of depression on quality of life became more pronounced, indicating a cumulative effect of chronic stress. Discussion. The findings are consistent with international studies that report heightened vulnerability of medical students to psycho-emotional disorders during pandemics and armed conflict. An increased role of depression as a predictor of lower quality of life was observed in 2024. Declines in self-control and optimism, combined with increased tension, suggest exhaustion of adaptive resources, particularly among men. Conclusions. Despite the stability of the general quality of life index, psycho-emotional components varied significantly depending on the time period and gender. Depression, anxiety, and disordered eating behavior remain key factors contributing to reduced quality of life among medical students. Implementation of psychological screening and support programs within educational institutions is necessary to identify at-risk groups in a timely manner. Key words: quality of life, mental health, stress, war, anxiety, depression, eating behavior, medical students УДК 616.89-008.441.3:613.95:378.6-057.875:316.62